Taxa de concepção de vacas em lactação submetidas à iatf utilizando dispositivos intravaginais com 1,0 e 1,3 g de progesterona - Lopes, Marco Antonio Ruiz [UNESP] (2015)
We compared the conception rate of dairy cows (22.4 ± 5,58L) submitted to TAI, using intravaginal device with different doses of progesterone (P4). The cows were randomly implanted with a device of 1.0g (n = 43) or 1.3 g P4 (n = 48) was then given 2 mg of estradiol benzoate (EB, MI). In D3 blood was collected for analysis of P4 concentration. In D8 was removed and the implant was administered 0.15 mg of D-cloprostenol (IM). At D9, was injected 1 mg of EB (MI) and about 56 h after implant removal was performed TAI. Ambient temperature was collected in the 50 days prior to insemination. Pregnancy diagnosis was performed with ultrasound after 30 days of TAI. The pregnancy rate was 19.8%, eight cows with 1.0g and ten with 1.3 g of P4. There was no difference in pregnancy rates between P4 groups and the presence or absence of CL (2 test). The maximum ambient temperature in the 50 days before IATF was higher (ANOVA) in patients not pregnant with 1.3 g of P4 in relation to non-pregnant with 1.0g and pregnant with 1.0 or 1.3 g of P4. For each increase of 1°C in average ambient temperature of 50 days pre AI pregnancy rate decreases 42.1% (logistic regression analysis). It was concluded that further lactating cow (22L) over intravaginal P4 (1 or 1.3 g) did not change the design rate with artificial insemination protocol used under these environmental conditions